On-Chip DNA Assembly via Dielectrophoresis - Xichuan Rui; Lin-Sheng Wu; Xin Zhao (Micromachines)
On-chip gene synthesis has the potential to improve the synthesis throughput and reduce the cost exponentially. While there exist several microarray-based oligo synthesis technologies, on-chip gene assembly has yet to be demonstrated. This work introduces a novel on-chip DNA assembly method via dielectrophoresis (DEP) that can potentially be integrated with microarray-based oligo synthesis on the same chip. Our DEP chip can selectively manipulate oligos and guide their movement without perturbing the surrounding fluid medium, thus aiding in DNA assembly. Helical forked electrode design has been optimized for compatibility with DEP, ensuring efficient control over target oligos. By applying an alternating current signal set at 2 MHz, we successfully achieve the desired directed movement of oligonucleotides. Additionally, chemical treatments combined with photoirradiation enabled the connection of complementary gene sequences and the subsequent release of single-stranded DNA products. Sequencing results validate the effective assembly of DNA fragments, approximately 500 base pairs in length, using our DEP device.